Distribution of Sea Surface Temperature and Salinity in the Karimata Strait - Yuliardi, Amir Yarkhasy; Firdaus, Randi; Heltria, Septy; Prayogo, Luhur Moekti; Nugroho, Agung Tri; Rahmalia, Diah Ayu; Sari, Ratna Juita (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
The Karimata Strait possesses unique characteristics influenced by its geographical location and the local, regional, and global impacts on its physical, biological, and chemical parameters, contributing to its potential as a significant fishing ground. This study aims to observe and analyze the physical oceanographic parameters, including temperature, salinity, and sea surface currents, within the Karimata Strait. The dataset comprises monthly averaged data, resulting in a single representative value for each month. Key physical parameters examined include temperature, salinity, and the horizontal (u) and vertical (v) current components. The patterns of sea surface temperature (SST) and salinity distribution in the Karimata Strait exhibit significant variations between the west and east monsoons. During the west monsoon season, the South China Sea influenced the region with lower SST and higher salinity than the Java Sea. In contrast, the east monsoon demonstrates an inverse pattern with warmer, fresher waters from the Java Sea moving towards the strait. Additionally, the horizontal distribution of these parameters highlights the critical role of sea currents in dispersing physical oceanographic characteristics within the region. These findings underscore the dynamic nature of the Karimata Strait's oceanography, influenced by seasonal monsoon shifts, water masses from adjacent seas, and freshwater inputs from rivers, crucial for understanding the broader Indonesian Throughflow (ITF) system and its implications for regional climate and marine ecosystems